Constitution of the National Assembly: Between normative and real - Pejić, Irena (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2024)
The constitution of the National Assembly, when examined within the normative framework, gives rise to numerous questions pertaining to the complete legitimization of the constitutive process of the highest representative body. According to the parliamentary Rules of Procedure, the first session of the National Assembly encompasses activities that are categorized into two groups. The first group of activities includes the confirmation of mandates of parliamentary deputies, the election of the President and Vice Presidents of the National Assembly, and the appointment of the General Secretary. The second group of activities typically unfolds during the inaugural session and involves the selection of the working bodies of the National Assembly, as well as the appointment of members to permanent parliamentary delegations in international organizations. Consequently, the Rules of Procedure establish a distinction in the potency of constitutive acts and actions, deeming the verification of mandates and the election of leadership as mandatory during the first session, while the selection of working bodies and the formation of parliamentary groups may occur “as a rule”, without binding deadlines. The normative framework allows for a flexible interpretation of constitutional deadlines set for the constitution of the National Assembly and the election of the Government (30 and 90 days). Thus, conditions are created for a “political game” that could significantly jeopardize the constitutional mechanism of organizing power, as evidenced in several parliamentary legislatures, including the current fourteenth, where the 30-day deadline elapsed without the election of the President of the National Assembly.